A high fatigue-resistant material for buffer blocks and its preparation method

By optimizing the material composition and preparation process, a high fatigue resistance material for buffer blocks was developed, which solved the problems of fatigue cracks and performance degradation of traditional materials under high frequency and high load conditions, and achieved significant improvement in the stability and durability of the material.

CN119775758APending Publication Date: 2025-04-08TIANJIN ZHIHUI TECH DEV CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411850637.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-16
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

Traditional buffer block materials are prone to fatigue cracks and performance degradation under high frequency and high load conditions, resulting in the impact of equipment stability and safety, and insufficient weather resistance, so they cannot cope with harsh environments.

Method used

A high fatigue resistance material is adopted, and its composition includes a matrix material, reinforcement fibers, fillers, fatigue resistance additives, crosslinking agents, antioxidants, weather resistance enhancers and flame retardants. By optimizing the material composition and preparation process, a buffer block material with excellent fatigue resistance is formed.

Benefits of technology

This material takes into account the advantages of the foam material's light weight, good impact resistance, energy absorption and buffering performance, and has the advantages of high strength and good wear resistance. It significantly improves the stability and durability of the buffer block and can maintain good performance during long-term use.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119775758A_ABST
    Figure CN119775758A_ABST
Patent Text Reader

Abstract

The present invention belongs to the field of equipment technology, and in particular, is a high fatigue resistance material for a buffer block and a preparation method thereof, including a base material, reinforcing fibers, fillers, fatigue resistance additives, crosslinking agents, antioxidants, weather resistance enhancers, and flame retardants. The present invention optimizes the material composition and preparation process, and the material takes into account the advantages of light weight, good impact resistance, energy absorption, and good buffering performance of foam materials and high strength and good wear resistance of elastomers, and has excellent flexibility and air permeability. The material has excellent mechanical properties and fatigue resistance, which can significantly improve the stability and durability of the buffer block under long-term use; the addition of reinforcing fibers and nano-silicon powder fillers enhances the overall rigidity and strength of the material, while maintaining good toughness, and at the same time adds antioxidants, weather resistance enhancers, and flame retardants, so that the material has good environmental adaptability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of equipment material science, and in particular to a high fatigue resistance material for a buffer block and a preparation method thereof. Background Art

[0002] Buffer blocks are widely used in mechanical equipment, transportation, aerospace and other fields, and they undertake important functions such as shock absorption and energy absorption.

[0003] As an important component of mechanical devices, buffer blocks are usually used for shock absorption, pressure reduction and buffering. During long-term use, they are often subject to repeated loads.

[0004] Traditional cushioning materials, such as rubber and polyurethane, have good elasticity and shock absorption performance, but they are prone to fatigue damage under high-frequency and high-load working conditions, resulting in weakened cushioning effect or even failure.

[0005] When used in the automotive industry, it is a device that can limit the maximum deformation of the suspension, which reduces the direct impact of the axle on the frame (or body) and prevents excessive deformation of the elastic element;

[0006] For example, shock absorbers in automobile suspension systems, buffers in rail transit, vibration-damping materials in aircraft wings, etc., all require materials with good fatigue resistance to ensure safety and reliability during long-term use. Since most of the traditional materials currently used have shortcomings such as short fatigue life, insufficient resistance to high temperature and high pressure, and obvious aging problems, the development of a new material with excellent fatigue resistance has become an urgent problem to be solved in the field of materials.

[0007] The prior art has the following defects or problems:

[0008] 1. Traditional buffer block materials are prone to fatigue cracks and performance degradation during repeated compression and release, which affects the overall stability and safety of the equipment. At the same time, their weather resistance cannot be guaranteed and they cannot cope with relatively harsh environments.

[0009] 2. With the rapid development of industrial technology, the requirements for buffer block materials are also increasing. The compression fatigue resistance and service life of existing materials do not meet the requirements, and parts are frequently replaced, which affects customer use and increases the cost of use. It is necessary to develop a new material with high fatigue resistance to meet market demand.

[0010] It should be noted that the above contents belong to the technical knowledge of the inventor and do not necessarily constitute prior art. Summary of the invention

[0011] In view of the deficiencies in the prior art, the present invention provides a high fatigue resistance material for a buffer block and a preparation method thereof, which solves the existing problems.

[0012] To achieve the above object, the present invention provides the following technical solution: A high fatigue resistance material for a buffer block, comprising the following raw materials by weight:

[0013] 75-85 parts of matrix material, 5-10 parts of reinforcing fiber, 5-10 parts of filler, 5-10 parts of anti-fatigue additive, 10-15 parts of cross-linking agent, 1-3 parts of antioxidant, 2-5 parts of weather resistance enhancer and 2-5 parts of flame retardant.

[0014] As a preferred technical solution of the present invention, the base material adopts a high-performance polymer material, which is specifically a polyurethane microporous elastomer, the reinforcing fiber is specifically glass fiber, the filler is specifically nano-silicon powder, the anti-fatigue additive is specifically nano-scale silica inorganic particles, the cross-linking agent is selected from one of diisocyanate and polyisocyanate, the antioxidant is specifically a phosphite antioxidant, the weather resistance enhancer includes a low-temperature plasticizer and a heat-resistant enhancer, the low-temperature plasticizer is specifically an organosilicon plasticizer, the heat-resistant enhancer is specifically polytetrafluoroethylene, and the flame retardant is specifically an aluminum hydroxide inorganic flame retardant.

[0015] Another technical problem to be solved by the present invention is to provide a method for preparing a high fatigue resistance material for a buffer block, comprising the following steps:

[0016] Step 1: Weigh each raw material and set aside for later use;

[0017] Step 2: placing the base material in a reaction kettle and heating it to a softened state;

[0018] Step 3: Place the reinforcing fiber and filler into a heat-insulating reactor, and stir them through an external stirring device so that they are fully mixed into the softened matrix material to form component A;

[0019] Step 4: Place the anti-fatigue additive, cross-linking agent, antioxidant, weather resistance enhancer and flame retardant into another set of reaction kettles, and stir them through an external stirring device to make the additives evenly mixed to form component B;

[0020] Step 5: Stir and blend the A / B group at a specific temperature so that the components are fully dispersed and gradually cross-linked;

[0021] Step 6: Process the mixed materials by casting to form a buffer block material of the required shape, and perform in-mold vulcanization at the same time.

[0022] In some of the embodiments, the softening temperature of the matrix material is controlled at 100-150 degrees Celsius, and is carried out by slow heating.

[0023] In some of the embodiments, the stirring speed of the external stirring device needs to be controlled between 50-300 rpm, and the filler is placed in the reactor, and the internal temperature thereof can soften the filler.

[0024] In some of the embodiments, the stirring speed of the stirring device needs to be controlled between 150-450 rpm, and the interior of the reactor needs to be evacuated by a vacuum pump to prevent the internal raw materials from contacting with the air.

[0025] In some of the embodiments, the stirring and blending temperature is controlled at 65-80 degrees Celsius.

[0026] In some of the embodiments, the in-mold vulcanization temperature needs to be controlled at 100-150 degrees Celsius and the time is 10 minutes.

[0027] Compared with the prior art, the present invention provides a high fatigue resistance material for a buffer block and a preparation method thereof, which has the following beneficial effects:

[0028] A high fatigue resistance material for a buffer block and a preparation method thereof, by optimizing the material composition and preparation process, the material takes into account the advantages of light weight, good impact resistance, energy absorption, good buffering performance of the foam material and high strength and good wear resistance of the elastomer, and has excellent flexibility and air permeability, excellent mechanical properties and anti-fatigue characteristics of the material, and can significantly improve the stability and durability of the buffer block under long-term use;

[0029] The material itself has good fluidity and operability, which is convenient for casting and molding, making the overall preparation process easier to implement;

[0030] The addition of reinforcing fibers and nano-silicon powder fillers enhances the overall rigidity and strength of the material while maintaining good toughness. At the same time, the addition of antioxidants, weather resistance enhancers and flame retardants makes the material have good environmental adaptability. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 The present invention is a schematic flow chart of a method for preparing a high fatigue resistance material for a buffer block. DETAILED DESCRIPTION

[0032] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0033] See also Figure 1 , Embodiment 1:

[0034] A high fatigue resistance material for a buffer block, comprising the following raw materials by weight:

[0035] 75 parts of matrix material, 5 parts of reinforcing fiber, 10 parts of filler, 5 parts of anti-fatigue additive, 10 parts of cross-linking agent, 1 part of antioxidant, 2 parts of weather resistance enhancer and 3 parts of flame retardant;

[0036] The matrix material is a high-performance polymer material, which is specifically a polyurethane microporous elastomer, the reinforcing fiber is specifically glass fiber, the filler is specifically nano-silicon powder, the anti-fatigue additive is specifically nano-scale silica inorganic particles, the cross-linking agent is a diisocyanate cross-linking agent, the antioxidant is specifically a phosphite antioxidant, the weather resistance enhancer includes a low-temperature plasticizer and a heat-resistant enhancer, the low-temperature plasticizer is specifically a silicone plasticizer, the heat-resistant enhancer is specifically polytetrafluoroethylene, and the flame retardant is specifically an aluminum hydroxide inorganic flame retardant.

[0037] Based on the above-mentioned high fatigue resistance material for a buffer block, a preparation method of the high fatigue resistance material for a buffer block is proposed, comprising the following steps:

[0038] Step 1: Weigh each raw material and set aside for later use;

[0039] Step 2: placing the base material in a reaction kettle and heating it to a softened state;

[0040] The softening temperature of the base material is controlled at 100 degrees Celsius, and the heating is carried out slowly;

[0041] Step 3: Place the reinforcing fiber and filler into a heat-insulating reactor, and stir them through an external stirring device so that they are fully mixed into the softened matrix material to form component A;

[0042] The stirring speed of the external stirring equipment should be controlled between 150rpm, and the filler is placed in the reactor, and the internal temperature can soften the filler;

[0043] Step 4: Place the anti-fatigue additive, cross-linking agent, antioxidant, weather resistance enhancer and flame retardant into another set of reaction kettles, and stir them through an external stirring device to make the additives evenly mixed to form component B;

[0044] The stirring speed of the stirring equipment must be controlled within 250rpm, and the interior of the reactor must be evacuated by a vacuum pump to prevent the internal raw materials from contacting with the air;

[0045] Step 5: Stir and blend the A / B group at a specific temperature so that the components are fully dispersed and gradually cross-linked;

[0046] The stirring and blending temperature was controlled at 65 degrees Celsius;

[0047] Step 6: Process the mixed materials by casting to form a buffer block material of the required shape, and perform in-film vulcanization at the same time;

[0048] The in-mold vulcanization temperature needs to be controlled at 100 degrees Celsius and the time is 10 minutes.

[0049] Embodiment 2:

[0050] A high fatigue resistance material for a buffer block, comprising the following raw materials by weight:

[0051] 85 parts of matrix material, 10 parts of reinforcing fiber, 5 parts of filler, 10 parts of anti-fatigue additive, 10 parts of cross-linking agent, 1 part of antioxidant, 5 parts of weather resistance enhancer and 4 parts of flame retardant;

[0052] The matrix material is a high-performance polymer material, which is specifically a polyurethane microporous elastomer, the reinforcing fiber is specifically glass fiber, the filler is specifically nano-silicon powder, the anti-fatigue additive is specifically nano-scale silica inorganic particles, the cross-linking agent is a polyisocyanate cross-linking agent, the antioxidant is specifically a phosphite antioxidant, the weather resistance enhancer includes a low-temperature plasticizer and a heat-resistant enhancer, the low-temperature plasticizer is specifically a silicone plasticizer, the heat-resistant enhancer is specifically polytetrafluoroethylene, and the flame retardant is specifically an aluminum hydroxide inorganic flame retardant.

[0053] Based on the above-mentioned high fatigue resistance material for a buffer block, a preparation method of the high fatigue resistance material for a buffer block is proposed, comprising the following steps:

[0054] Step 1: Weigh each raw material and set aside for later use;

[0055] Step 2: placing the base material in a reaction kettle and heating it to a softened state;

[0056] The softening temperature of the base material is controlled at 120 degrees Celsius, and the heating is carried out slowly;

[0057] Step 3: Place the reinforcing fiber and filler into a heat-insulating reactor, and stir them through an external stirring device so that they are fully mixed into the softened matrix material to form component A;

[0058] The stirring speed of the external stirring equipment should be controlled between 180rpm. The filler is placed in the reactor, and the internal temperature can soften the filler;

[0059] Step 4: Place the anti-fatigue additive, cross-linking agent, antioxidant, weather resistance enhancer and flame retardant into another set of reaction kettles, and stir them through an external stirring device to make the additives evenly mixed to form component B;

[0060] The stirring speed of the stirring equipment must be controlled between 240rpm, and the inside of the reactor must be evacuated by a vacuum pump to prevent the internal raw materials from contacting with the air;

[0061] Step 5: Stir and blend the A / B group at a specific temperature so that the components are fully dispersed and gradually cross-linked;

[0062] The stirring and blending temperature is controlled at 75 degrees Celsius;

[0063] Step 6: Process the mixed materials by casting to form a buffer block material of the required shape, and perform in-film vulcanization at the same time;

[0064] The in-mold vulcanization temperature needs to be controlled at 120 degrees Celsius and the time is 10 minutes.

[0065] Each embodiment in this specification is described in a progressive manner, and the same or similar parts between the embodiments can be referred to each other, and each embodiment focuses on the differences from other embodiments. In particular, for the system embodiment, since it is basically similar to the method embodiment, the description is relatively simple, and the relevant parts can be referred to the partial description of the method embodiment.

[0066] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A high fatigue resistance material for a buffer block, characterized in that: The raw materials include the following weight fractions: 75-85 parts of matrix material, 5-10 parts of reinforcing fiber, 5-10 parts of filler, 5-10 parts of anti-fatigue additive, 10-15 parts of cross-linking agent, 1-3 parts of antioxidant, 2-5 parts of weather resistance enhancer and 2-5 parts of flame retardant.

2. The high fatigue resistance material for a buffer block according to claim 1, characterized in that: The matrix material is a high-performance polymer material, which is specifically a polyurethane microporous elastomer, the reinforcing fiber is specifically glass fiber, the filler is specifically nano-silicon powder, the anti-fatigue additive is specifically nano-scale silica inorganic particles, the cross-linking agent is selected from one of diisocyanate and polyisocyanate, the antioxidant is specifically a phosphite antioxidant, the weather resistance enhancer includes a low-temperature plasticizer and a heat-resistant enhancer, the low-temperature plasticizer is specifically an organosilicon plasticizer, the heat-resistant enhancer is specifically polytetrafluoroethylene, and the flame retardant is specifically an aluminum hydroxide inorganic flame retardant.

3. A method for preparing a high fatigue resistance material for a buffer block, characterized in that: The steps include: Step 1: Weigh each raw material and set aside for later use; Step 2: placing the base material in a reaction kettle and heating it to a softened state; Step 3: Place the reinforcing fiber and filler into a heat-insulating reactor, and stir them through an external stirring device so that they are fully mixed into the softened matrix material to form component A; Step 4: Place the anti-fatigue additive, cross-linking agent, antioxidant, weather resistance enhancer and flame retardant into another set of reaction kettles, and stir them through an external stirring device to make the additives evenly mixed to form component B; Step 5: Stir and blend the A / B group at a specific temperature so that the components are fully dispersed and gradually cross-linked; Step 6: Process the mixed materials by casting to form a buffer block material of the required shape, and perform in-mold vulcanization at the same time.

4. The method for preparing a high fatigue resistance material for a buffer block according to claim 1, characterized in that: In step 2, the softening temperature of the base material is controlled at 100-150 degrees Celsius, and is carried out by slow heating.

5. The method for preparing a high fatigue resistance material for a buffer block according to claim 3, characterized in that: The stirring speed of the external stirring device in step 3 needs to be controlled between 50-300 rpm. The filler is placed in the reactor, and the internal temperature thereof can soften the filler.

6. The method for preparing a high fatigue resistance material for a buffer block according to claim 3, characterized in that: The stirring speed of the stirring equipment in step 4 needs to be controlled between 150-450 rpm, and the interior of the reactor needs to be evacuated by a vacuum pump to prevent the internal raw materials from contacting with the air.

7. The method for preparing a high fatigue resistance material for a buffer block according to claim 3, characterized in that: The stirring and blending temperature in step 5 is controlled at 65-80 degrees Celsius.

8. The method for preparing a high fatigue resistance material for a buffer block according to claim 3, characterized in that: The in-mold vulcanization temperature in step 6 needs to be controlled at 100-150 degrees Celsius and the time is 10 minutes.